Thymic Stromal Lymphopoietin in Cutaneous Immune-Mediated Diseases - Wang, Si-Hang; Zuo, Ya-Gang (Frontiers in Immunology, 2021)
Thymic stromal lymphopoietin (TSLP) was initially demonstrated to be critical in regulating inflammatory responses among various allergic disorders (such as atopic dermatitis, food allergy, and asthma). Although two isoforms (short form and long form) of TSLP have been demonstrated in human tissues, the long form of TSLP (lfTSLP) is strongly implicated in the pathogenesis of allergies and cutaneous immune-mediated diseases. The immunomodulatory activity of lfTSLP varies widely, driving T helper (Th) cells polarizing Th2 and Th17 immune responses and inducing itch. Moreover, lfTSLP is closely associated with skin fibrosis, epidermal hyperplasia, angiogenesis, and homeostatic tolerogenic regulations. This review highlights significant progress from experimental and clinical studies on lfTSLP in cutaneous immune-mediated diseases (atopic dermatitis, psoriasis, bullous pemphigoid, systemic sclerosis, chronic spontaneous urticaria, Behçet's disease, vitiligo, rosacea, systemic lupus erythematosus, and alopecia areata). We also offer original insights into the pleiotropic properties of the cytokine TSLP in various pathophysiological conditions, with significant clinical implications of TSLP-targeted therapies for immune-mediated skin diseases in the future.